(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction Talaromyces marneffei formerly known as Penicillium marneffei, is the only dimorphic fungus within the Talaromyces genus capable of causing systemic mycosis in humans, significantly contributing to mortality among HIV/AIDS patients. Due to its non-specific clinical and paraclinical manifestations, the disease is frequently misdiagnosed as other infectious pathologies, leading to delayed treatment and increased mortality rates. Methods A retrospective study was conducted on 30 patients diagnosed with Talaromyces marneffei infection and treated at the National Lung Hospital from January 2024 to September 2025. Subjects were divided into two groups: HIV-positive [HIV(+)] and HIV-negative [HIV(-)] to compare clinical characteristics, laboratory findings, and mortality rates. Results The HIV(+) group (n=9) was significantly younger than the HIV(-) group (38,44 ± 10,0 vs. 55,29 ± 12,7 years; p = 0,002). Clinically, HIV(+) patients exhibited a markedly higher prevalence of diarrhea (77,8%), umbilicated skin papules (77,8%) and splenomegaly (33,3%) compared to the HIV(-) group (p < 0,05). Regarding laboratory findings, no statistically significant differences were found between the two groups ( p > 0,05). However, the HIV(+) group showed a trend toward lower white blood cell counts ( 8,1 ± 7,4 G/L vs. 15,0 ± 9,6 G/L; p = 0,064). The overall mortality rate was 23,3%, with the HIV(+) group showing a higher trend compared to the HIV(-) group ( 33,3% vs. 19,0% ; p > 0,05). Disscusion and Conclusion Clinical manifestations of Talaromyces marnerffei infection differ significantly between the two groups. HIV(+) patients typically present with a robust systemic disease including skin papules, diarrhea, and organ involvement (liver, spleen). Conversely, the HIV(-) group predominantly exhibits respiratory symptoms, often mimicking pulmonary tuberculosis or respiratory diseases. High mortality rates in both groups, particularly in HIV(+) patients, underscore the critical importance of early diagnosis and prompt antifungal intervention.